2009
DOI: 10.1093/jat/33.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Urinary Drug Concentrations with Specific Gravity and Creatinine

Abstract: Excessive fluid intake can substantially dilute urinary drug concentrations and result in false-negative reports for drug users. Methods for correction ("normalization") of drug/metabolite concentrations in urine have been utilized by anti-doping laboratories, pain monitoring programs, and in environmental monitoring programs to compensate for excessive hydration, but such procedures have not been used routinely in workplace, legal, and treatment settings. We evaluated two drug normalization procedures based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(108 citation statements)
references
References 14 publications
8
96
0
1
Order By: Relevance
“…A creatinine-corrected value will correct for a patient's hydration on the day of the test and show a decrease in the amount of nordiazepam in the urine, thus supporting the patient's claim that he or she has stopped taking the drug. It is important that reference laboratories not only provide creatininecorrected results but that they give doctors or staff help in interpreting the data (Cone et al, 2009). It is also important for the physician to know if a patient has attempted to obscure UDT results by diluting a urine specimen.…”
Section: Interpretation Of Udt Resultsmentioning
confidence: 99%
“…A creatinine-corrected value will correct for a patient's hydration on the day of the test and show a decrease in the amount of nordiazepam in the urine, thus supporting the patient's claim that he or she has stopped taking the drug. It is important that reference laboratories not only provide creatininecorrected results but that they give doctors or staff help in interpreting the data (Cone et al, 2009). It is also important for the physician to know if a patient has attempted to obscure UDT results by diluting a urine specimen.…”
Section: Interpretation Of Udt Resultsmentioning
confidence: 99%
“… Some laboratories, in particular in area of doping controls, concentrated (spiked) urine samples or special normalization procedures that are based on specific gravity and creatinine content within the measured urine are recommended for accurate urine drug testing programs [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, reports prove that ratios in a light or infrequent user will decrease faster than those in a heavy or frequent user. Cone et al 33 reported on normalization of cocaine urine testing results to urine creatinine. Quantitative benzoylecgonine (BE) to urine creatinine levels allowed for the differentiation of positive BE levels arising from washout and from positive BE levels resulting from new cocaine use.…”
Section: Discussionmentioning
confidence: 99%